The efficacy of high-intensity, focused ultrasound treatment for non-neoplastic epithelial disorders of the vulva - Zhou, W; Zhu, L; Zhou, H; Shen, K; Lang, J; Cui, Q; Shi, H (Cellular and Molecular Biology, 2016)
Non-neoplastic epithelial disorders of the vulva (NNEDV) are common types of vulval lesions. Although corticosteroids represent a first-line treatment for NNEDV, concerns exist about the safety associated with long-term topical corticosteroid use. Recently, several clinical trials have identified high-intensity focused ultrasound (HIFU) as a promising treatment modality for NNEDV. The aim of this multi-center, randomized, controlled clinical trial was to investigate the efficacy of HIFU therapy in women with NNEDV based on histological alterations. We enrolled patients who were clinically diagnosed with NNEDV. They were randomized into 2 treatment groups: 1) halcinonide for 3 months or 2) HIFU once. A total of 123 patients were biopsied both prior to and after the therapy, and 62 and 61 patients were assigned to the HIFU and halcinonide groups, respectively. The histological changes were then analyzed. After the treatments, the therapeutic effects were observed in both groups. Comparing the diagnosis and alterations in lichenoid and sclerotic patterns and in chronic inflammation, we found statistically significant differences. Furthermore, when compared with the halcinonide group, the HIFU group exhibited enhanced curative effects that were statistically significant (P = 0.039). Based on the histological evidence from this randomized, controlled trial, HIFU represents an effective method for the treatment of NNEDV.